2022
DOI: 10.3390/nu14153060
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Lifestyle-Induced Weight Loss Determines the Risk of Prediabetes and Metabolic Syndrome Recurrence during a 5-Year Follow-Up

Abstract: It is controversial whether lifestyle-induced weight loss (LIWL) intervention provides long-term benefit. Here, we investigated whether the degree of weight loss (WL) in a controlled LIWL intervention study determined the risk of prediabetes and recurrence of metabolic syndrome (MetS) during a 5-year follow-up. Following LIWL, 58 male participants (age 45–55 years) were divided into four quartiles based on initial WL: Q1 (WL 0–8.1%, n = 15), Q2 (WL 8.1–12.8%, n = 14), Q3 (WL 12.8–16.0%, n = 14), and Q4 (WL 16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 45 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, these findings highlight the possibility that weight loss of ≥7.5%, at least ≥5.0%, would be desirable for patients with obesity to improve obesity-related CVD risk components in the first 3 months to 5 years. In this context, a previous study reported that weight loss within the first two months predicted long-term weight loss for up to 8 years ( 23 ), further suggesting the significance of optimizing the outcome during early intervention periods to exhibit long-term beneficial effects ( 8 ). Moreover, obesity exacerbates MetS ( 24 ), thereby highlighting the need to achieve weight loss to counterbalance the detrimental effects of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accordingly, these findings highlight the possibility that weight loss of ≥7.5%, at least ≥5.0%, would be desirable for patients with obesity to improve obesity-related CVD risk components in the first 3 months to 5 years. In this context, a previous study reported that weight loss within the first two months predicted long-term weight loss for up to 8 years ( 23 ), further suggesting the significance of optimizing the outcome during early intervention periods to exhibit long-term beneficial effects ( 8 ). Moreover, obesity exacerbates MetS ( 24 ), thereby highlighting the need to achieve weight loss to counterbalance the detrimental effects of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term maintenance of weight loss has been challenging because weight is typically lost rapidly by intervention but followed by progressive regain ( 8 , 12 ); it is reported that ≥90% of individuals regained some of the weight after weight loss ( 25 , 26 ). In the present study, outpatients with obesity continuously underwent physician-supervised intervention for up to 5 years, and 47.7%, 39.1%, and 24.1% of these patients achieved ≥3.0%, ≥5.0%, and ≥7.5% weight loss from baseline at the 5-year follow-up, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations